To simplify the expression \( -7(9x - 5) \), we need to distribute \(-7\) to both terms inside the parentheses:
-
Distribute \(-7\) to \(9x\): \[ -7 \cdot 9x = -63x \]
-
Distribute \(-7\) to \(-5\): \[ -7 \cdot -5 = +35 \]
Putting it together, we get: \[ -7(9x - 5) = -63x + 35 \]
Now let's evaluate the provided statements:
A. First, distribute −7.
Correct: This is the first step to simplify the expression.
B. First, calculate −7 + (−5).
Incorrect: This does not represent a valid step in simplifying the expression.
C. −7(9x − 5) = −63x − 35.
Incorrect: The sign in front of the \(35\) is wrong; it should be \(+35\).
D. −7(9x − 5) = −63x + 35.
Correct: This is accurate based on our simplification.
E. −7(9x − 5) = 63x − 35.
Incorrect: Both the coefficient of \(x\) and the constant term have incorrect signs.
Thus, the correct statements are A and D.